Perception of riverside folk about environmental degradation in the Igaraçu river, Piauí, Brazil - Vieira, Irlaine Rodrigues; Aguiar, Maria Rikelly Frota; Amarante, Luiz Henrique Machado; Sales, Manoel Bruno Alves; Virapongse, Arika; Oliveira, Jefferson Soares de (Sociedade & Natureza, 2023)
Co-development of knowledge is a useful tool for addressing the management of complex social-ecological systems like the ribeirinhos (riverine communities) of Brazil. Incorporating local knowledge and environmental perception of ribeirinhos into assessments of river degradation can lead to management outcomes that better support human and ecosystem health. In the state of Piauí, Brazil, riverine people depend on the Igaraçu River for various subsistence needs. However, river pollution has increased. The objective of this study was to comprehend the perceptions of ribeirinhos regarding the environmental degradation of the Igaraçu River in Piauí and how they believed it affected their life and ecosystem. We conducted interviews with 79 informants to gather insights on environmental degradation, its causes, and consequences. The results were analyzed using a Loyalty Level (LL) metric. The majority of respondents (67.86%, n=38) perceived that degradation was indeed taking place. They attributed the primary causes of degradation to discarded garbage (LL= 74.41) and the discharge of polluted water (LL= 11.60). Informants reported that local fauna and flora (LL= 35.70) were being impacted by water contamination. However, despite their reliance on the river for sustenance, including food, water, and the harvesting of forest products, they did not perceive any significant harm to their livelihoods. This study demonstrates that individuals who have a direct dependency on local natural resources can offer firsthand data regarding environmental changes. However, additional efforts are required to assist local communities (those who directly utilize the local environment) in developing a deeper understanding of how environmental degradation impacts both the present and future of their communities, as well as their connection to the local ecosystem.